Recovering sodium erythorbate from wastewater through freeze crystallization technology. (10th February 2019) - Chen, Peng; Song, Pengfei; Wang, Lidong; Yan, Ying; Liu, Yongdi; Zhang, Lehua
Abstract: Eutectic freeze crystallization was developed to recover sodium erythorbate (NaE) from wastewater at pHs 4.1, 5.3, and 6.5. Two substances (A and B) were sequentially recovered from the samples. The recovery rate of substance A was 2.06, 1.83, and 3.03 g/L at pHs 4.1, 5.3, and 6.5, respectively; while that of B was 5.51, 3.09, and 3.26 g/L at the corresponding pHs. The analysis results of the two recovered substances indicated that substance A was mostly Na2 SO4 ·10H2 O, while substance B was mainly NaE. Salt recovery was most successful at pH 4.1 with the purity of recovered NaE reaching 87.53 wt%. Moreover, the chemical oxygen demand and electric conductivity of the ice were far smaller than the initial wastewater. The concentration effect was minimal due to the formation of Na2 SO4 ·10H2 O and NaE crystals. This combined crystallization strategy can potentially become an economic technology to recover NaE from wastewater. Practitioner points Segregation of NaE and Na2 SO4 ·10H2 O during the freeze crystallization process. Recovering 5.53 kg NaE with the purity of 87.53 wt% from 1 m 3 wastewater. Decreasing chemical oxygen demand and electric conductivity of wastewater through freeze crystallization technology. Abstract : Both sodium erythorbate (NaE) and Na2 SO4 ·10H2 O are recovered from wastewater using the freeze crystallization processes. Meanwhile, the wastewater is cleaned by recovering the ice thawing water.